1986
DOI: 10.1093/oxfordjournals.aje.a114430
|View full text |Cite
|
Sign up to set email alerts
|

Life-Style and Occupational Risk Factors in Cancer of the Lower Urinary Tract

Abstract: In a matched case-control study of cancer of the lower urinary tract in northern Germany in which 340 male and 91 female case-control pairs were interviewed between 1977 and 1982, cigarette smokers were found to have an odds ratio of 2.3 for males and 2.9 for females compared with nonsmokers. A significant dose-response relation was observed for increasing cigarette consumption, and a significant decrease in risk was shown for ex-smokers. Employment in rubber, plastics, dye, textiles, and mining industries was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
94
2
11

Year Published

1992
1992
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(116 citation statements)
references
References 0 publications
7
94
2
11
Order By: Relevance
“…High consumption of fluids may reduce this exposure. One prospective study demonstrated this negative association (28), whereas other studies reported positive associations (13,(29)(30)(31)(32)(33) or no association (15,34). Correction for total water intake did not change the results substantially.…”
Section: Discussionmentioning
confidence: 98%
“…High consumption of fluids may reduce this exposure. One prospective study demonstrated this negative association (28), whereas other studies reported positive associations (13,(29)(30)(31)(32)(33) or no association (15,34). Correction for total water intake did not change the results substantially.…”
Section: Discussionmentioning
confidence: 98%
“…A number of case -control studies have examined the possible association of UTIs with bladder cancer in developed countries (Howe et al, 1980;Kantor et al, 1984;Claude et al, 1986;Piper et al, 1986;Kjaer et al, 1989;Gonzalez et al, 1991;La Vecchia et al, 1991;Sturgeon et al, 1994;Jhamb et al, 2007). The overall evidence supports an increased risk from UTIs.…”
Section: Discussionmentioning
confidence: 99%
“…An experimental study in rats has shown associations between chronic infections with Escherichia coli and early bladder neoplasia (Davis et al, 1991), and it has been suggested that the high rates of bladder cancer in some parts of Africa and the Middle East may be due to the high prevalence of chronic infection with Schistosoma haematobium (IARC, 1994). A review of published epidemiological studies regarding the association between bladder infections and transitional cell carcinoma (TCC), the predominant type in developed countries, shows inconsistent results (Howe et al, 1980;Kantor et al, 1984;Claude et al, 1986;Piper et al, 1986;Kjaer et al, 1989;Gonzalez et al, 1991;La Vecchia et al, 1991;Sturgeon et al, 1994;Jhamb et al, 2007) and reveals a need for future studies to determine whether UTIs increase the risk of bladder cancer.…”
mentioning
confidence: 99%
“…Alguns tipos específicos de cân-cer, para os quais foi observado um excesso de óbi-tos entre os eletricitários, como cavidade oral/faringe, laringe e bexiga, têm o fumo como importante fator de risco 11 . Os resultados para câncer de cérebro, contudo, não poderiam ser explicados facilmente pela presença desse tipo de fator de risco.…”
Section: Discussionunclassified
“…Os óbitos por doença de Hodgkin, embora em pequeno número, se concentraram também na categoria de maior exposição (Tabela 5). Por outro lado, como já foi mencionado, diversos trabalhos têm mostrado uma associação entre fumo ou álcool e câncer de bexiga 10,11,49 , e esses antecedentes não são conhecidos para o grupo de eletricitários, o que não permite afastá-los como possíveis fatores de distorção dos resultados.…”
Section: Discussionunclassified